2007
DOI: 10.2174/1573401310703010055
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Based Studies of Eating Among Children and Adolescents

Abstract: The prevalence of pediatric overweight has increased dramatically over the past three decades, likely due to changes in food intake as well as physical activity. Therefore, information examining eating patterns among children and adolescents is needed to illuminate which aspects of eating behavior require modification to prevent and treat pediatric overweight. Because child self-report and parentreport of children's eating habits are often inconsistent and limited by recall and other biases, laboratory-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 144 publications
(213 reference statements)
0
31
0
1
Order By: Relevance
“…Although intake during test meal studies has been shown to reflect eating behavior outside of the laboratory (27,28), another limitation is the possibility that such studies may not yield the same eating patterns that occur in the natural environment. Nevertheless, the benefits of laboratory studies include the carefully controlled testing environment, direct observation of eating behaviors, and precise measurements of energy intake (29). Such methods are better than questionnaire measures of intake, on which individuals frequently underestimate food consumption (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Although intake during test meal studies has been shown to reflect eating behavior outside of the laboratory (27,28), another limitation is the possibility that such studies may not yield the same eating patterns that occur in the natural environment. Nevertheless, the benefits of laboratory studies include the carefully controlled testing environment, direct observation of eating behaviors, and precise measurements of energy intake (29). Such methods are better than questionnaire measures of intake, on which individuals frequently underestimate food consumption (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Most observational studies on eating in toddlerhood have highlighted links with pathology (Tanofsky-Kraff et al, 2007). This research, in focusing on normality (A.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, Tanofsky-Kraff et al (2007) show that toddler and preschooler eating has been studied more than any other age group of children, claiming that toddlers can be observed "with little intrusion into their daily habits" p. 62).…”
Section: Eating In Toddlerhoodmentioning
confidence: 99%
“…One study available in the literature indicated that the liking a food is associated with the consumption of that food in young children (Tanofsky-Kraff, Haynos, Kotler, Yanovski, & Yanovski, 2007). Another, longitudinal study in young children's showed a strong relationship between children's intake and their liking of the food (Skinner, Carruth, Wendy, & Ziegler, 2002).…”
Section: Discussionmentioning
confidence: 99%